The interplay of voiceless and voiced sounds in Qabbani’s elegy immortalizing Balqis - Albatool Abalkheel; Maha Sourani (Cogent Arts & Humanities)
The elegy of Balqis holds a significant place in contemporary Arabic poetry, renowned for its length and magnificence. Within its verses lie encrypted structures and enigmatic ideas, challenging literary scholars to decode its symbols. Yet it has received relatively little scholarly attention concerning phono-semantics. To address this gap, this descriptive-analytical study deciphered many of the symbols and words within poetic texts and a prosodic analysis revealed the correlation between specific phonetic features (voiced and voiceless sounds) and the semantic content (themes, emotions) of the poem. Furthermore, to achieve scientific accuracy, this work calculated the percentage of voiced and voiceless sounds, gutturalization, for each poetic segment. Results revealed that the ratio of voiceless (1612 sounds = 17%) to voiced sounds (3204 sounds = 34%) in the elegy has deviated markedly from established speech patterns (5 to 20%), rendering the recorded percentage of these sounds notably elevated, or even exceedingly high. The current study holds significant importance as an extensive search of databases, including academic search engines, peer-reviewed journals, conference proceedings, and linguistic resources spanning the past decade, has not uncovered any previous attempts to analyze this specific elegy from a phono-semantic perspective. Finally, suggestions for future research are presented to serve as the foundation for forthcoming studies.